Targeting pancreatic beta cell death in type 2 diabetes by polyphenols - García-Aguilar, Ana; Guillén, Carlos (Frontiers in Endocrinology, 2022)
Diabetes is a very complex disease which is characterized by the appearance of insulin resistance that is primarily compensated by an increase in pancreatic beta cell mass, generating hyperinsulinemia. After time, pancreatic beta cells die by apoptosis appearing in the second phase of the disease, and characterized by hypoinsulinemia. There are multiple conditions that can alter pancreatic beta cell homeostasis and viability, being the most relevant ones; ER stress, cytotoxicity by amylin, mTORC1 hyperactivity, oxidative stress, mitochondrial dysfunction, inflammation and alterations in autophagy/mitophagy flux. In addition, the possible effects that different polyphenols could exert in the modulation of these mechanisms and regulating pancreatic beta cell viability are analyzed. It is necessary a profound analysis and understanding of all the possible mechanisms involved in the control and maintenance of pancreatic beta cell viability to develop more accurate and target treatments for controlling beta cell homeostasis and preventing or even reversing type 2 diabetes mellitus.